Bilateral Achilles Tendon Rupture Following A Fall from Height: Case Report - I Gede Bramantya Surya Mahendra; Dyah Purnaning (Indonesian Journal of Global Health Research, 2025)
Achilles tendon rupture is an injury characterized by partial or complete disruption of the Achilles tendon, commonly caused by trauma or a sudden change in foot position. This condition accounts for approximately 20% of all major tendon ruptures. This study aims to present and analyze a rare case of bilateral Achilles tendon rupture, emphasizing the clinical presentation, diagnostic challenges, and management considerations. Men are at 2–12 times higher risk than women, with the incidence increasing between the ages of 40 and 59 years. Diagnosis is established through history taking, physical examination, and imaging modalities such as ultrasonography or MRI. We report a case of a 53-year-old male who presented with pain and swelling in both posterior ankles for the past three months, following a fall from a height of approximately four meters. The patient experienced limited mobility and required a walking aid. Physical examination revealed bilateral edema, a palpable defect in the Achilles tendon, tenderness, a positive Thompson test, and weakness of plantar flexion. MRI confirmed bilateral Achilles tendon rupture. The patient had previously undergone conservative management, including the application of an ankle strap and administration of nonsteroidal anti-inflammatory drugs, with no improvement. Bilateral Achilles tendon rupture is a rare condition, typically resulting from high-energy trauma. Delayed diagnosis and treatment may increase the risk of complications and long-term disability. Management options include conservative or surgical approaches, selected based on patient age, extent of rupture, and activity level. Bilateral Achilles tendon rupture following a fall from height is an uncommon case, highlighting the importance of prompt diagnosis and appropriate treatment to prevent permanent functional impairment.